(untitled) (Bangladesh Medical Journal, 2012)
Kidney disease is one of the world’s major public health problems and the prevalence of kidney failure is rising day by day. The structure and function of the kidney changes with advancing age. This study is to find out the histological architecture of kidney in Bangladeshi people related to age. The study was descriptive type of cross-sectional study carried out in the Department of Anatomy, Mymensingh Medical College, Mymensingh, from July 2006 to June 2007. For this study 30 pairs of postmortem human kidneys of age ranging from 3 years to 60 years were selected. The kidneys were collected from dead bodies autopsied in the morgue of Mymensingh Medical College. The collected sample was divided into three age groups. They are as follows, group A (3-20 years), group B (21-40 years) and group C (41-60 years). All the samples were examined histologically by staining with Haematoxylin and Eosin stain. It was found that the number of renal corpuscles per square millimeter of both right and left kidney showed significant difference between group A and B (P<0.00), group B and C (P<0.00) and group A and C (P<0.000) . Diameter of renal corpuscles and renal glomeruli in μm of both right and left kidney showed significant difference between group A and B (P<0.00), group B and C (P<0.00) and group A and C (P<0.000). DOI: http://dx.doi.org/10.3329/bmj.v40i1.9956 BMJ 2011; 40(1): 13-17